Konsep Spiritual Quotient Menurut Danah Zohar dan Ian Marshall Dalam Perspektif Pendidikan Islam - Arin Muflichatul Matwaya; Ahmad Zahro (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Spiritual Quotient (SQ), which is the foundation needed to function Intelligent Quotient (IQ) and Emotional Quotient (EQ) effectively. Even SQ is the highest intelligence. So that humans who have high SQ are a category of people who have noble morals. So Islamic education will play a role in aspects of humanity which can actually be maximized through SQ sensitivity. This study is intended to answer the following problems: (1) What is the General Concept of Spiritual Quotient? (2) What is the Concept of Spiritual Quotient in the Perspective of Islamic Education? These problems are discussed through library data collection, reading, taking notes, and processing research materials. This scientific work is a type of library research research, which is a series of activities related to the methods of collecting library data, reading, taking notes, and processing research materials which are library research or pure research. All data were analyzed using a philosophical approach. This study shows that: (1) Spiritual intelligence (SQ) means the ability to know and understand ourselves fully as spiritual beings and as part of the universe. Having spiritual intelligence means that we fully understand the meaning and essence of the life we live and where humans are going. Based on these two concepts, it shows that Western SQ is more oriented towards the completion and achievement of world happiness, while Islamic SQ is more about achieving happiness in the world and the hereafter. If both are used ideally, SQ can be implemented in order to achieve "happiness" both in this world and in the hereafter. (2) The concept of Spiritual Quotient in the perspective of Islamic education is spirituality education that can sharpen the quality of spiritual intelligence, namely the values of spirituality itself which are aimed at education